Personnel management - Chruden, Herbert J.; Sherman, Arthur W. (Cincinnati : South-western Pub. Co., 1972)
This book provides the foundation for the contemporary theory and practices relating to the management of people. The book is devoted to behavioral science, in terms of both theory and application.
Includes bibliographical references and index
hza 18/07/2018
Loan
Keywords: Personnel management